The rise of the conservative legal movement : the battle for control of the law - Teles, Steven Michael (Princeton studies in American politics., 2008)
Starting in the 1970s, conservatives learned that electoral victory did not easily convert into a reversal of important liberal accomplishments, especially in the law. As a result, conservatives' mobilizing efforts increasingly turned to law schools, professional networks, public interest groups, and the judiciary--areas traditionally controlled by liberals. Drawing from internal documents, as well as interviews with key conservative figures, The Rise of the Conservative Legal Movement examines this sometimes fitful, and still only partially successful, conservative challenge to liberal domina.